Quantification of training load using session RPE method and performance in futsal - Victor Hugo Freitas; Bernardo Miloski; Maurício Gattas Bara Filho (Universidade Federal de Santa Catarina, 2011)
There is a need of studies about training load (TL) quantification using session rating of perceived exertion (session-RPE) and its relation to athlete's performance in futsal. The objective of this study was to describe training load behavior using session-RPE method and to analyze futsal athlete´s performance during a preparatory period and its relation to TL. Twelve male futsal players (age 24,92 ± 5,20 year, weight 73,42 ± 5,70 kg, height 175,83 ± 5,05 cm) were submitted to 14 weeks of training quantified by the session-RPE method. It was measured maximum volume of oxygen (VO₂max), velocity, agility and vertical jump (VJ) before and after the training period and also the VJ every week. Using the Wilcoxon test, it was observed an increase in VO₂max (p=0,004), VJ (p=0,003), velocity (p=0,003) and agility (p=0,002) after the training period. Using the ANOVA to repeated measures (Tukey post-hoc), it was observed a greater training load (TL) in the first mesocycle compared to the others and a greater CT in the second compared to the third mesocycle. It was not found a relation between VJ and TL. It was concluded that the session RPE allowed an effective TL quantification through the training period and the athlete's performance increased along with the progressive TL reduction description. There wasn't correlation between the TL and performance.